Scientific Argumentation Abilities among Undergraduate Biology Students: An Analysis Using the Toulmin’s Argument Pattern (TAP) Framework - Muhamad Justitia Ramadhan; Siti Zubaidah; Munzil Munzil (Jurnal Paedagogy, 2026)
This study aims to examine the level of scientific argumentation skills among biology students using Toulmin’s Argument Pattern (TAP) framework. The research employed a quantitative descriptive method using essay questions designed to elicit key components of scientific argumentation. The participants consisted of 82 undergraduate students enrolled in a Genetics course during the even semester of the 2025 academic year. Data were collected through an essay test developed based on Genetics-related topics. Data analysis focused on the presence of TAP components and the classification of students’ levels of scientific argumentation. The results reveal that students’ scientific argumentation skills remain low, with 47.56% of students categorized at Level 1 and 30.5% at Level 2. Analysis of TAP component distribution indicates that 91.46% of students were able to state claims; however, these claims were predominantly unsupported by warrants or reasoning that meaningfully connected the evidence to the conclusions. The low levels of scientific argumentation observed reflect limitations in students’ critical thinking and scientific reasoning skills. Therefore, the implementation of instructional models such as Problem-Based Learning (PBL), Project-Based Learning (PjBL), and TAP-guided formative assessment strategies is recommended to enhance students’ scientific argumentation abilities.